Hubungan Postur Ikan dengan Jumlah Endoparasit pada Ikan Tongkol (Auxis rochei) yang Didaratkan di Pantai Kedonganan, Bali - Putri, Annisa Millenia; Julyantoro, Pande Gde Sasmita; Pebriani, Dewa Ayu Angga (Current Trends in Aquatic Science; Vol 6 No 1 (2023), 2023)
This study aims to determine the various types of parasites that infect tuna, their abundance, prevalence, level of parasite intensity and the effect of fish length on the number of parasitic infections. Fish samples were obtained from Kedonganan Beach, Bali from November-December 2021. This study used a descriptive method and data collection using simple random sampling. The total samples examined were 35 fish. The endoparasites found in the internal organs of fish which include the intestines, liver, and gonads consist of 3 different genera, namely: Rhadinorhynchus sp., Anisakis sp., and Lecithocladium sp. The highest abundance was found in the genus Rhadinorhynchus sp., the highest prevalence was found in the genus Rhadinorhynchus sp., and the highest intensity level was found in the genus Lecithocladium sp. The relationship between length and number of parasites was classified as "very weak" because the correlation between the two relationships ranged from 0.00-0.199. So, it can be concluded from the research that has been done related to the relationship between fish posture and the number of endoparasites that infect the tuna ( Auxis rochei ) which was landed on the beach of Kedonganan, Bali. There is no relationship between fish body posture and the number of endoparasite infections or can be classified into the category of a "very weak" relationship.